Navigating the challenges of moving from research to clinical care: The example of the Teen Online Problem Solving program. - Glazer, Sandra; Bonanno, KellyAnn; Gies, Lisa; Cirincione, Lindsay; Moscato, Emily L; Winning, Adrien M; Leib, Sophie; Austin, Cynthia; Van Tubbergen, Marie; Johnson, Abigail; Hankin, Dina; McNally, Kelly; et al. (Journal of Pediatric Rehabilitation Medicine, 2026)
Purpose/Objective: The pathway from clinical trials to implementation is lengthy and often unsuccessful. Thus, identifying strategies that promote clinical implementation is necessary. The Framework for Reporting Adaptations and Modifications-Enhanced was employed to characterize adaptations to the Teen Online Problem Solving program (TOPS). The aim was to broaden program reach and adoption by aligning TOPS with the needs of the implementation context, extending delivery to a broader range of pediatric neurological conditions. Method: Providers completed surveys about commonly experienced neurocognitive challenges across diagnoses. Therapists delivering the program to non-traumatic brain injury (TBI) diagnoses were surveyed about their experiences. Reach to non-TBI diagnoses and adoption by therapists treating other diagnoses provided metrics of implementation impact. Results: Medical providers rated cognitive/communication issues as most common and identified physical limitations, concentration/attention problems, learning/school difficulties, planning/organization, and processing speed as top concerns. Twenty-five psychologists/trainees ranked the child's current neurocognitive challenges, mood and behavior concerns, and developmental level as the most important considerations for tailoring, with diagnosis ranked seventh. Of 828 patients enrolled, 354 had non-TBI diagnoses, and 245 had TBI. Four case studies illustrate adaptations. Conclusions/Implications: Findings suggest that transdiagnostic adaptation of evidence-based pediatric psychology programs may be acceptable to clinicians and facilitate broader implementation.